Replication Data for: Separating geometry- from stress-induced remanent magnetization in magnetite with ilmenite lamellae from the Stardalur basalts, Iceland - ter Maat, Geertje W. (DataverseNO, 2020)
Bulk rock magnetic measurements (hysteresis loops, backfield curves and FORC diagrams) were done on basalts from the Stardalur volcano. Realistic geometries of magnetite grains from those basalts were obtained by FIB-SEM nanotomography. Meshes of these geometries were used to create micromagnetic models. The magnetic properties of these grains were modeled using the three dimensional micromagnetic code MERRILL and the influence of grain shape and size were isolated by modeling hysteresis loops. Comparing the modeled hysteresis loops with measured bulk hysteresis loops allows for quantification of internal stress in these grains. This dataset includes the meshes used to do the micromagnetic modeling, the resulting hysteresis loop data, and the raw data files for the rock magnetic measurements.